2018
DOI: 10.1111/gtc.12593
|View full text |Cite
|
Sign up to set email alerts
|

CD109 deficiency induces osteopenia with an osteoporosis‐like phenotype in vivo

Abstract: Osteoporosis is a global public health problem that is increasing along with an aging population. A major determinant of osteoporosis is high bone turnover, which results from osteoclast activation. CD109 is a glycosylphosphatidylinositol-anchored glycoprotein, a deficiency that leads to a psoriasis-like skin inflammation in mice. Although the expression of CD109 has been reported in mouse pre-osteoclast cells, its function in osteoclasts in vivo remains largely unknown. To investigate the physiological role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 38 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…These findings suggest that CD109‐deficient mice exhibit a “high‐turnover osteoporosis” phenotype (Fig. b) . Paradoxically, CD109 deficiency reduced osteoclast formation in pre‐osteoclast cells in vitro .…”
Section: Cd109 Is a Membrane Protein Expressed In Malignant Tumorsmentioning
confidence: 85%
See 4 more Smart Citations
“…These findings suggest that CD109‐deficient mice exhibit a “high‐turnover osteoporosis” phenotype (Fig. b) . Paradoxically, CD109 deficiency reduced osteoclast formation in pre‐osteoclast cells in vitro .…”
Section: Cd109 Is a Membrane Protein Expressed In Malignant Tumorsmentioning
confidence: 85%
“…Additionally, CD109‐deficient mice exhibited an osteopenia phenotype that was verified by reduced bone/tissue volume, decreased trabecular number, and increased trabecular separation according to microcomputed tomography (micro‐CT) scans (Fig. a) . IHC analysis showed that CD109 is expressed in both osteoblasts and osteoclasts, and serum analyses revealed that CD109 deficiency increases their activities in mice .…”
Section: Cd109 Is a Membrane Protein Expressed In Malignant Tumorsmentioning
confidence: 90%
See 3 more Smart Citations